Pengaruh Beban Kerja terhadap Motivasi dengan Burnout sebagai Variabel Mediasi di Telkom Indonesia Kandatel Bali - Putri, Anak Agung Raka Nita Trisna; Anggreni, Putri; Dewi, Ni Putu Yuli Tresna (ARZUSIN, 2023)
Human Resources (HRD) is one of the subsystems that has an important role in improving public health status through various health efforts and services. The purpose of this research is to analyze burnout to mediate the effect of workload on work motivation at Telkom Indonesia Kandatel Bali. This research uses the type of associative research. The research design used in this study is to use a quantitative descriptive method of survey methods. The research location used in this research is Telkom Indonesia Kandatel Bali, which is located at Jl.Kaliasem 2 Denpasar. The population in this study were 75 employees at Telkom Indonesia Kandatel Bali. So that the sample in this study were 75 employees. The data analysis technique in this study uses Partial Least Square (PLS). Based on the research above. The workload variable has a negative effect on work motivation. Workload variables affect burnout. The burnout variable has a negative effect on motivation. Workload has a negative effect on motivation through burnout.